The beard of the Bearded Vulture (Gypaetus barbatus): citizen science suggests an adjustable airflow sensor - Tiziano Londei (Rivista Italiana di Ornitologia - Research in Ornithology)
The beard of the Bearded Vulture is part of a facial mask of prominent bristles that extends under the bill with two tufts between the mandibular rami. The function of this unique beard is still unclear. The facial bristles of birds are simple feathers, probably similar to the feathers that may have served a tactile function since the origin of all birds. Although their present-day functions are generally poorly understood, facial bristles have mechanoreceptors near their follicles, as in the case of filoplumes located at the base of flight feathers, an apparatus with proven sensitivity to airflow. Citizen science is increasingly providing a great number of Bearded Vulture images, some of which already allow us to suppose that these birds adjust the projection of the beard, relative to the bill line, depending on flying conditions. This viewpoint might produce further hypotheses, e.g., that the longer beards of the adult birds might serve their visibly more agile flight and that the likely ornamental function in sexual/social displays might be an added function to the primary, sensory role of the facial bristles, both of which would be enhanced by the length of the beard.